How COVID-19 changed frontline healthcare workers' experiences: A narrative inquiry into the impact of chronic burnout on a surgical physician assistant's wellness - Lihua Dishman; Rhionna Smith (The Beryl Institute, 2023)
Burnout is an occupational phenomenon resulting from unmanaged chronic workplace stress. Since COVID-19 started, burnout among healthcare workers has worsened and become a public health crisis. Wellness is about leading a physically, mentally, and spiritually healthy lifestyle to achieve one's full potential through positive affirmations. Its multiple dimensions include (1) physical, (2) emotional, (3) intellectual, (4) occupational, (5) social, and (6) spiritual. Extant empirical literature lacked regarding surgical physician assistants and how chronic burnout affected their wellness. This longitudinal narrative inquiry thus aimed to explore the perceived impact of a surgical physician assistant's chronic burnout during the COVID-19 pandemic on her physical, mental, and emotional wellness through her lived work experiences from the onset to the major surges of COVID-19 positive cases (2020, 2021, 2022). The study participant provided the researcher with her self-recorded personal journals of lived work experiences. The researcher organized and re-presented the narratives, applied thematic analyses to identify key dimensions from the narratives, and grouped them into positive-effect and negative-effect dimensions. Three positive-effect dimensions were (1) resilience and healthcare leadership competencies, (2) work support system, and (3) family-and-friend support system. Six negative-effect dimensions were (1) lack of federal leadership and coordination, (2) unhealthy work conditions, (3) caring for the critically ill, (4) inequity in work-location arrangements, (5) frustrated and angry patients and families, and (6) increased workload. Healthcare policymakers and industry leaders must pay immediate attention to the Quintuple Aim's 4th and 5th aims to address healthcare workers' burnout and wellness, and inequity within the healthcare workforce. Experience Framework This article is associated with the Staff & Provider Engagement lens of The Beryl Institute Experience Framework (https://theberylinstitute.org/experience-framework/). Access other PXJ articles related to this lens. Access other resources related to this lens.